A Legal Analysis of Simple Verification and Legal Protection for Concurrent Creditors in the Bankruptcy of a Developer (A Case Study of Decision No. 20/Pdt.Sus-Pailit/2022/PN.Niaga.Smg) - Safitri, Diana Alpiani; Rahmatiar, Yuniar; Abas, Muhamad (Dinasti Research, 2025)
Bankruptcy is a legal mechanism that provides certainty for creditors when debtors are no longer able to fulfill their payment obligations. This study aims to analyze the legal steps that creditors can take against debtors who are in default based on the Cooperation Agreement Deed, as well as to examine the judge's considerations in deciding bankruptcy cases in the Semarang District Court Decision No. 20/Pdt.Sus-Pailit/2022/PN.Niaga.Smg in accordance with Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. The research method used is normative juridical with a constitutional and case approach. The results of the study indicate that the bankruptcy petition was granted because the bankruptcy requirements were met, namely the presence of more than one creditor and debts that had matured as regulated in Article 2 paragraph (1) of the PKPU Law. The panel of judges emphasized the principle of pari passu pro rata parte and the application of the principle of simple proof based on Article 8 paragraph (4) of the PKPU Law as the basis for their considerations. In conclusion, the application of the principle of simple proof in bankruptcy cases effectively provides legal certainty while guaranteeing justice for the parties.